Development and evaluation of an integral sliding mode fault‐tolerant control scheme on the RECONFIGURE benchmark. (25th October 2017) - Chen, L.; Alwi, H.; Edwards, C.
Summary: This paper describes the development, application, and evaluation of a linear parameter‐varying integral sliding mode control allocation scheme to the Reconfiguration of Control in Flight for Integral Global Upset Recovery benchmark model to deal with an actuator failure/fault scenario. The proposed scheme has the capability to maintain close to nominal (fault free) load factor control performance in the face of elevator failures/faults by including a retrofitted integral sliding mode term and then rerouting (via control allocation) the augmented control signal to healthy elevators without reconfiguring the baseline controller. In order to mitigate any chattering appearing in the elevator demands, the retrofitted signal is based on a super‐twisting sliding mode structure. This produces a control signal that is continuous and does not have the discontinuous switching nature of traditional sliding mode schemes. The scheme is evaluated using an industrial Functional Engineering Simulator developed as part of the Reconfiguration of Control in Flight for Integral Global Upset Recovery project. Monte Carlo campaign results are shown to demonstrate the performance of the proposed scheme.